A Comparative Study of Attitudes Toward Sustainability in the Ecuador-Colombia Border Integration Zone - Almeida, Luis Homero Viveros; Solarte, Claudia Magali Solarte (Journal of Posthumanism, 2026)
This study analyzes differences in attitudes toward sustainability among business owners in the Ecuador-Colombia Border Integration Zone (ZIF), specifically in the provinces of Carchi (Ecuador) and Nariño (Colombia). The study employed a quantitative, descriptive, and correlational cross-sectional approach. The research examines whether there are significant differences in attitudes toward sustainability, considering variables such as gender, educational background, economic sector, and country of operation. The results reveal statistically significant differences by gender and country, while academic background and economic sector did not show conclusive differences. These findings contribute to the understanding of the factors involved in the adoption of sustainability practices in cross-border contexts and provide important information for the formulation of government policies aimed at promoting corporate sustainability in the region.